African religions as “parables of the Kingdom”? Karl Barth and Kwame Bediako on revelation and culture - Hartman, Tim (Stellenbosch theological journal, 2019)
This article engages Swiss theologian Karl Barth’s understanding of true words of revelation coming through cultural media (“parables of the Kingdom” in Church Dogmatics IV/3, §69.2) in juxtaposition with Ghanaian theologian Kwame Bediako’s understanding of African traditional religions as “evangelical preparation” for the Christian faith, claiming that since God has been active among Africans for millennia, Africans have been worshipping the same God as Christians. In contrast, Barth understands Jesus Christ to be prophetically proclaiming a message of good news that opposes many (Western) cultural assumptions. Barth’s understanding of Jesus Christ as the “Light of Life” serves to desacralize the Christian community and the Biblical Scriptures and collapses the categories of “sacred” and “profane.” Eliminating this binary categorization opens the possibility of affirming traditional African religions as media of revelation.